Adenosine A2A and dopamine D2 receptor interaction controls fatigue resistance - Alves, Ana Cristina de Bem; Santos, Naiara de Souza; Santos, Ana Paula Tavares; Panatta, Gabriela da; Speck, Ana Elisa; Cunha, Rodrigo A.; Aguiar, Aderbal S. (Frontiers in Pharmacology, 2024)
Caffeine and the selective A2A receptor antagonist SCH58261 both have ergogenic properties, effectively reducing fatigue and enhancing exercise capacity. This study investigates in male Swiss mice the interaction between adenosine A2A receptors and dopamine D2 receptors controlling central fatigue, with a focus on the striatum where these receptors are most abundant. We employed DPCPX and SCH58261 to antagonize A1 and A2A receptors, caffeine as a non-competitive antagonist for both receptors, and haloperidol as a D2 receptor antagonist; all compounds were tested upon systemic application and caffeine and SCH58261 were also directly applied in the striatum.Behavioral assessments using the open field, grip strength, and treadmill tests allowed estimating the effect of treatments on fatigue. The results suggested a complex interplay between the dopamine and adenosine systems. While systemic DPCPX had little effect on motor performance or fatigue, the application of either caffeine or SCH58261 was ergogenic, and these effects were attenuated by haloperidol. The intra-striatal administration of caffeine or SCH58261 was also ergogenic, but these effects were unaffected by haloperidol. These findings confirm a role of striatal A2A receptors in the control of central fatigue but suggest that the D2 receptor-mediated control of the ergogenic effects of caffeine and of A2A receptor antagonists might occur outside the striatum. This prompts the need of additional efforts to unveil the role of different brain regions in the control of fatigue.